Factors affecting purchase intentions in generation y: An empirical evidence from fast food industry in Malaysia - Aiyun Xiao; Shaohua Yang; Qaisar Iqbal (Administrative Sciences, 2019)
The purpose of the present study was to investigate the factors that influence the purchase intentions of Generation Y students towards the fast food industry in Nilai, Malaysia. Nowadays, purchase intentions are an important aspect of organizational long-term success in the fast food industry. In addition, purchase intentions are the critical element in competing with other competitive environments; hence, it is important for the fast food industry to pay a significant attention to this matter. The present study was conducted to identify the key determinants that impact the purchase intention of Generation Y students towards the fast food industry in Nilai, Malaysia. Employing the quantitative method in this study, a total of 313 questionnaires were distributed with the response rate of 91%. Another purpose of this study was to provide important insights to Nilai fast food restaurants in understanding the purchase intentions of customers. Therefore, the leaders and managers of Nilai local fast food restaurants can enhance customers' experience, solve their problems, and ultimately obtain high quality business by understanding the key factors of purchase intentions in fast food industry.
Keywords: 350; service quality; purchase intention; Generation Y; food industry; Malaysia; price